First report of an olive ridley (Lepidochelys olivacea) inside the Mediterranean Sea - REVUELTA, O.; CARRERAS, C.; DOMÈNECH, F.; GOZALBES, P.; TOMÁS, J. (Mediterranean Marine Science, 2015)
We report the first confirmed occurrence of a Lepidochelys olivacea in the Mediterranean Sea based on the study of an individual stranded on a beach, located in the town of Oropesa del Mar (40º05ʹ32ʺN, 0º08ʹ02ʺE), Castellón province, East Spain, in May 2014. Morphological and genetic analyses were used to confirm the identification of the species. The individual had a sequence that matched the 470 bp Lepidochelys olivacea haplotype F (Genbank accession number: AF051773), found in several Atlantic populations. This becomes one of the northernmost known occurrences of olive ridleys in the world and is the first reports of this species in the Mediterranean Sea.